2019
DOI: 10.5582/irdr.2019.01064
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and clinical manifestations of rare genetic disorders associated with type I collagen

Abstract: Type I collagen is an important structural protein of bone, skin, tendon, ligament and other connective tissues. It is initially synthesized as a precursor form, procollagen, consisting of two identical pro-α1(I) and one proα2(I) chains, encoded by COL1A1 and COL1A2, respectively. The N-and C-terminal propeptides of procollagen are cleavage by N-proteinase and C-proteinase correspondingly, to form the central triple helix structure with Gly-X-Y repeat units. Mutations of COL1A1 and COL1A2 genes are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 106 publications
0
20
0
9
Order By: Relevance
“…Previous studies categorize OI into four subtypes (types I–IV) based on clinical findings, inheritance patterns, and radiographic features: OI type I is the mildest form, OI type II is the perinatal lethal form, while OI type III is the most severe form, and OI type IV is characterized by the mild to moderate form (Sillence et al, 1979; Rauch et al, 2010; Lin et al, 2015; Mrosk et al, 2018). With an in-depth understanding of OI disease, more subtypes have been defined and added into OI’s original classification system, making the number of subtypes updated to 18 (Forlino and Marini, 2016; Marini et al, 2017; Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies categorize OI into four subtypes (types I–IV) based on clinical findings, inheritance patterns, and radiographic features: OI type I is the mildest form, OI type II is the perinatal lethal form, while OI type III is the most severe form, and OI type IV is characterized by the mild to moderate form (Sillence et al, 1979; Rauch et al, 2010; Lin et al, 2015; Mrosk et al, 2018). With an in-depth understanding of OI disease, more subtypes have been defined and added into OI’s original classification system, making the number of subtypes updated to 18 (Forlino and Marini, 2016; Marini et al, 2017; Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Osteogenesis imperfect (OI), also known as brittle bone disease, is a genetic connective tissue disorder with genetic and phenotypic diversity (Friedrich, Scheuer & Holtje, 2019;Subramanian & Viswanathan, 2019). Nearly 85% of OI patients belong to type I to type IV of OI, which is induced by COL1A1 and COL1A2 genes encoding proα1(I) and proα2(I) of type I procollagen in an autosomal-dominant inherited form (Lu et al, 2019). Type II collagen is of major importance in endochondral bone formation, growth, and normal joint function, and one of the clinical manifestations of type II collagen disease is skeletal dysplasia (Gregersen & Savarirayan, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Its variants may also partially affect the development of valves and their proper functioning. It has been demonstrated that osteogenesis imperfecta in humans, which is characterized by a tendency for bone fractures, is caused by mutations in either the COL1A1 or COL1A2 genes encoding type I collagen [ 15 ]. It should also be noted that these patients sometimes develop aortic dissection [ 28 ] and, in addition, cases of the Ehlers-Danlos heart valve syndrome associated with genetic variants in various COL1A1 -related genes have been described [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The type I collagen-related diseases are characterized by a wide spectrum of diseases and high clinical variability, whose genetic basis is still poorly understood. Several candidate genes have been identified as being associated with thoracic aortic aneurysms and bicuspid aortic valve (BAV) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%